EFEKTIVITAS PENURUNAN KADAR AMONIAK DAN KADAR FOSFAT DI INSTALASI PENGOLAHAN AIR LIMBAH RSUD SUNAN KALIJAGA DEMAK - Tatag Kurnia Putra; Sulistyani Sulistyani; Mursid Rahardjo; Suhartono Suhartono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Level of ammonia and phosphate content of liquid waste of RSUD Sunan Kalijaga Demak exceeded the quality standard as stipulated in Central Java Regulation no. 5 Year 2012. High levels of ammonia and phosphate levels can cause a decrease in environmental quality. This study aims to determine the effectiveness of decreased levels of ammonia and phofate levels in the waste water treatment plant RSUD Sunan Kalijaga Demak.This type of research is observational. The population in this research is effluent of liquid waste RSUD Sunan Kalijaga Demak and sample consist of 80 liters effluent of liquid waste. The average sampling result showed that the ammoniac inlet level was 0.26 mg / l and the ammonia outlet level was 0.15 mg / l so that there was a decrease of ammonia content of 40.68%. As for the phosphate inlet level of 14.96mg / l and phosphate outlet 2.67 mg / l so that there was a decrease in phosphate content of 82.16%.The results of this study indicate that the processing of WWTP in the waste water treatment plant RSUD Sunan Kalijaga Demak has been effective in levels of ammonia and phosphate levels in RSUD Sunan Kalijaga Demak. Based on different test, ammonia level before treatment is different with after processing with significance value 0,007 smaller than α = 0,05. While the phosphate levels before treatment is different with after processing with a significance value of 0.004 smaller than α = 0.05. The results of this study indicate that the effluent treatment using chlorine is effective to reduce the ammonia and phosphate levels